2012
DOI: 10.1186/1758-3284-4-4
|View full text |Cite|
|
Sign up to set email alerts
|

Etiology analysis and computed tomography imaging of a tonsillar inflammatory myofibroblastic tumor: report of an immunocompetent patient and brief review

Abstract: ObjectivesThe etiology of Inflammatory myofibroblastic tumor(IMT) is contentious. In this study, we used computed tomography (CT) to examine tonsillar IMT and further analyzed the etiology of this entity.MethodologyWe presented CT features of left tonsillar IMT and reviewed the English-language literature published between 1984 and 2011.ResultsTo our knowledge, there are only six published cases of tonsillar IMT including the present case. Two patients were asymptomatic at initial presentation. Two patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In our study, all masses were solid and no evidence of cystic or necrotic change was found. Despite their apparently benign morphological nature, IMTs have been reported to have locally aggressive growth behavior (10,14). In our study, 80% (8/10) of the masses had aggressive, lobulated appearances, with unclear margins on MRI.…”
Section: Discussionmentioning
confidence: 62%
“…In our study, all masses were solid and no evidence of cystic or necrotic change was found. Despite their apparently benign morphological nature, IMTs have been reported to have locally aggressive growth behavior (10,14). In our study, 80% (8/10) of the masses had aggressive, lobulated appearances, with unclear margins on MRI.…”
Section: Discussionmentioning
confidence: 62%